2010
DOI: 10.1264/jsme2.me09184
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bacterial Community Composition in the System of Rice Intensification (SRI) in Chiang Mai, Thailand

Abstract: The factors of alternating flooding and draining during the vegetative growth phase and applying compost to investigate changes in bacterial community composition between the system of rice intensification (SRI) and conventionally managed rice were investigated. 16S rRNA gene T-RFLP analysis showed the major changes in the bacterial communities from the beginning of cultivation to vegetative phase, at which time the groups formed remained consistent until the end of cropping season. Significant and consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition, organic matter addition was able to increase AMF hyphae growth (17, 14). Sooksa-nguan and colleagues (32) also revealed changes in microbial communities in which differences in rice cultivation systems affected the structures of Bacteria and Archaea communities. This suggest that the SRI practice, where flooding was alternated with periods of draining, allowed for higher O 2 availability in the soil with higher AMF establishment than conventionally managed practice, while the addition of compost might favor nutrients as well as being a growth condition that could induce diversity of AMF.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, organic matter addition was able to increase AMF hyphae growth (17, 14). Sooksa-nguan and colleagues (32) also revealed changes in microbial communities in which differences in rice cultivation systems affected the structures of Bacteria and Archaea communities. This suggest that the SRI practice, where flooding was alternated with periods of draining, allowed for higher O 2 availability in the soil with higher AMF establishment than conventionally managed practice, while the addition of compost might favor nutrients as well as being a growth condition that could induce diversity of AMF.…”
Section: Discussionmentioning
confidence: 97%
“…Sooksa-nguan et al [32] reported changes in microbial communities in which differences in rice cultivation systems affected the structures of bacterial and archaeal communities. At the highest root colonization and AMF spore density stage of rice plants (9 weeks) under non-sterilized soil conditions, the total culturable bacteria and fungi count were highest in AMF biofertilizer-added pots, and the microbial count was lowest under sterilized soil conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In trials conducted in northern Thailand, the community structures of bacteria and archaea showed significant changes under SRI practice as compared with what was found in conventionally-managed rice fields. Community compositions of these soil microbes started to change during the vegetative phase of rice growth, just after the practice of alternating wetting and drying of SRI plots began; and the microbial communities continued to diverge between the two respective strategies until the water management for both systems was made the same again just before harvesting ( Sooksa-Nguan et al., 2010 ). This indicated that bacterial and archaeal communities were responding quite differently to the regime for water management.…”
Section: The Diverse and Dynamic Structure Of Microbial Communities U...mentioning
confidence: 99%